ASSESSMENT OF THE ANTICANCER ACTIVITY OF RUBUS ELLIPTICUS AGAINST COLON CANCER CELLS HCT-116 - Rohid Rasheed (PT. Radja Intercontinental Publishing, 2025)
This study explores the historical significance, pharmacological potential, and therapeutic efficacy of medicinal plants in treating chronic diseases and cancer. Leveraging traditional knowledge and modern scientific approaches, we investigate a variety of medicinal plants, including Achyranthes aspera, Moringa oleifera, and Rubus ellipticus, to elucidate their antioxidant, antibacterial, and anticancer properties. Comprehensive phytochemical screenings reveal diverse bioactive compounds, such as phenolics, flavonoids, and alkaloids, which contribute to their therapeutic actions. The study also delves into the molecular mechanisms underpinning the anticancer activities of these plants, highlighting their roles in modulating immune responses and inhibiting cancer cell proliferation. Additionally, the research underscores the significance of integrative oncology, emphasizing the need for combining conventional treatments with herbal medicine to enhance clinical outcomes and reduce side effects. The findings advocate for the conservation of medicinal plant biodiversity and suggest avenues for future research to validate and expand the use of these natural resources in modern medicine. This holistic approach aims to bridge the gap between traditional practices and contemporary medical science, fostering the development of novel, effective, and sustainable therapeutic options for global health challenges.